Efektivitas Penggunaan Kitab at-Tuḥfah as-Saniyyah dalam Pembelajaran Nahwu - Fahita (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the teaching of Arabic grammar using the book at-Tuhfah as-Saniyyah in class XI at Miftahul Huda Al-Ulya Islamic Boarding School in Kalijambe Sragen during the 2025-2026 academic year. at-Tuḥfah as-Saniyyah is a commentary (syarh) on Matn al-Ājurūmiyyah. at-Tuḥfah as-Saniyyah explains Arabic rules in clear, detailed, and that is easy for beginner student to understand. Since Arabic grammar serves as the primary foundation for understanding Arabic texts, selecting an appropriate instructional material is crucial. This study was motivated by the need to determine the extent to which at-Tuḥfah as-Saniyyah is able to assist students in comprehending nahwu subject matter. The method employed was a descriptive qualitative approach, which aims to describe learning phenomena as they naturally occur. Research data were collected through classroom observation, learning outcome assessments, and interviews with the teacher. The findings indicate that learning using at-Tuḥfah as-Saniyyah is effective in helping students understand nahwu, as evidenced by the fact that only two students scored below the minimum passing grade while 25 students achieved scores above it. Nevertheless, the uneven distribution of midterm assessment scores suggests that continuous review of material and practice exercises remain necessary to ensure that students’ understanding of nahwu develops comprehensively.